2018
DOI: 10.1155/2018/6363474
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Fuzziness in CDS Pricing under a Structural Model

Abstract: OTC credit derivatives are nonstandardized financial derivatives which have the following characteristics. (1) Information on trades is not public. (2) There is no performance guarantee from the stock exchange. (3) The bigger the risk in performance, the bigger the price floating. These result in an asymmetry of market information flow and this asymmetry acts as a decisive factor in the credit risk pricing of financial instruments. The asymmetry of market information flows will lead to obvious fuzziness in how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Kijima and Muromachi [6] considered the pricing of the k-to-default basket CDS, but they did not give a clear solution. Wu et al [7] proposed a new model for evaluating the value of credit default swap contracts subject to multiple credit risks. Tey showed that default dependence has a signifcant impact on CDS pricing.…”
Section: Introductionmentioning
confidence: 99%
“…Kijima and Muromachi [6] considered the pricing of the k-to-default basket CDS, but they did not give a clear solution. Wu et al [7] proposed a new model for evaluating the value of credit default swap contracts subject to multiple credit risks. Tey showed that default dependence has a signifcant impact on CDS pricing.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and He [6] proposed the multi-scale stochastic volatility (SV) model to price a CDS. Based on the structural model and introducing the concept of fuzziness, Wu et al [7] proposed a new double exponential jump diffusion model with fuzziness for CDS pricing.…”
Section: Introductionmentioning
confidence: 99%
“…Kijima and Muromachi [17] considered k th -to-default basket CDS pricing, but they did not give the explicit solution. White [7] presented a new model for valuing a CDS contract which was affected by multiple credit risks. ey showed that the default dependency had a significant impact on CDS pricing.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and He [3] proposed the multiscale stochastic volatility (SV) model to price the CDS premium. Under the framework of structural model, Wu et al [26] proposed a new double exponential jump-diffusion model with fuzziness for CDS pricing. He and Lin [11] derived an analytical approximation for the price of a CDS contract price by assuming that the reference asset followed a regime switching Black–Scholes model.…”
Section: Introductionmentioning
confidence: 99%